BUDGETARY FAIRNESS DAN KESENJANGAN ANGGARAN DI PEMERINTAH DAERAH BANGKA BARAT - Hadi Mahmudah (JRAK: Journal of Accounting Research and Computerized Accounting, 2016)
This study examines the effect of the budgeting system design against the tendency middle managers to create budgetary slack. The purpose of this study is to test the design of the budgeting system to reduce the propensity to create budgetary slack in government. Data were obtained through a survey to middle manager in west Bangka local governments. The data were processed using SPSS with a sample size of 60. The result showed that the unfair budgeting system design did not significantly affect budgetary slack Contributions of this study is to give feedback to the authorities to design budgeting system for efficiency in government budgets.